Liver ASK1 protects from non‐alcoholic fatty liver disease and fibrosis. Issue 10 (6th June 2019) - Challa, Tenagne D; Wueest, Stephan; Lucchini, Fabrizio C; Dedual, Mara; Modica, Salvatore; Borsigova, Marcela; Wolfrum, Christian; Blüher, Matthias; Konrad, Daniel
Abstract: Non‐alcoholic fatty liver disease (NAFLD) is strongly associated with obesity and may progress to non‐alcoholic steatohepatitis (NASH) and liver fibrosis. The deficit of pharmacological therapies for the latter mainly results from an incomplete understanding of involved pathological mechanisms. Herein, we identify apoptosis signal‐regulating kinase 1 (ASK1) as a suppressor of NASH and fibrosis formation. High‐fat diet‐fed and aged chow‐fed liver‐specific ASK1‐knockout mice develop a higher degree of hepatic steatosis, inflammation, and fibrosis compared to controls. In addition, pharmacological inhibition of ASK1 increased hepatic lipid accumulation in wild‐type mice. In line, liver‐specific ASK1 overexpression protected mice from the development of high‐fat diet‐induced hepatic steatosis and carbon tetrachloride‐induced fibrosis. Mechanistically, ASK1 depletion blunts autophagy, thereby enhancing lipid droplet accumulation and liver fibrosis. In human livers of lean and obese subjects, ASK1 expression correlated negatively with liver fat content and NASH scores, but positively with markers for autophagy. Taken together, ASK1 may be a novel therapeutic target to tackle NAFLD and liver fibrosis. Synopsis: Liver‐specific ASK1 expression blunts obesity‐associated hepatic steatosis and liver fibrosis potentially through induction of autophagy. Thus, ASK1 may be a novel therapeutic target to tackle NAFLD and liver fibrosis. Liver‐specific deletion of apoptosis signal‐regulating kinase 1 (ASK1) aggravated high fat diet and age‐induced hepatic steatosis, inflammation and fibrosis in mice. Liver‐specific ASK1 overexpression protected mice from the development of high fat diet‐induced hepatic steatosis and carbon tetrachloride‐induced fibrosis. ASK1 depletion blunts autophagy thereby enhancing lipid droplet accumulation. ASK1 may prevent the development of obesity‐associated hepatic steatosis and liver fibrosis through induction of autophagy. Abstract : Liver‐specific ASK1 expression blunts obesity‐associated hepatic steatosis and liver fibrosis potentially through induction of autophagy. Thus, ASK1 may be a novel therapeutic target to tackle NAFLD and liver fibrosis.